Modality in President Jokowi’s Speech at the Arab Islamic American Summit in Riyadh - Majid Ariyoga (Universitas Sebelas Maret, 2024)
Terrorism was the main issue discussed by state leaders attending the Arab Islamic American Summit of 2017 in Riyadh, Saudi Arabia. One of those leaders who attended and delivered his speech was President Jokowi. He delivered his speech on Indonesians’ experiences in facing and countering terrorism and radicalism. This study aimed to reveal President Jokowi's attitude on terrorism and radicalism issues expressed by modality in his speech. It was conducted by applying the Systemic Functional Linguistics approach. Previous studies on modality have been conducted by many scholars. However, this study was essentially the development of those studies. In addition, this study applied different methods and focused on a particular issue, namely terrorism and radicalism. The result of this study showed that three types of modality, namely obligation, inclination, and probability were found in President Jokowi’s speech. Besides, it also uncovered terrorism discourses involving the impacts of terrorism and the strategies to counter terrorism.